IMPROVING STUDENTS' WRITING SKILL THROUGH TEXT REPORT AT THE FIRST YEAR OF SMA MUHAMMADIYAH 5 JUWIRING - NISAK , CHAIRUN (2007)
This research is aimed to know whether or not the students ha ve adequqte writing skill in learning English, to know the students participation during English teaching learning process using text report to improve students' writing skill, and to describe the achievement of the students writing skill in their test result. The result of this study hopefully will give contribution in learning English. In this research, text report is used to improve students' writing skill in learning English. This research was carried out at Sma Muhammadiyah 5 Juwiring especially in cla ss B that consist of 35 Students. To collect the requierd data, the writer did observation, gave test, and used interview. There were two cycles in this action research. In which each cycle used pretest and post test. The result of pretest and post test we re used to know the score of the writing skill. The mean score of pre test 57.71 That belongs to low score. While, the mean score of the students writing skill of the teacher did the action was 80.28 Based on the research findings, it can be concluded that the result of the students' achievement showed that descriptive paragraph using text report in teaching writing could improve the students' achievement better. The students score was getting better in each cycle. It indicated that the teaching leraning process was successful. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in learning English. While the English teacher should teach the students with text report, process considerable knowledge to manage an interesting classroom, and prepare the lessons they are going to teach as well as possible.